Transfer of tasks in work disability assessments in European social security. Issue 1 (March 2020) - de Wind, Annette E.; Brage, Sören; Latil, Francois; Williams, Nerys
European social security organisations experience shortages of insurance physicians and they attempt to streamline procedures in the disability assessment services in order to save costs, while safeguarding the quality of the assessments. Hence, they look at alternative ways for efficient and cost-effective assessments by transferring insurance physician tasks to other (non)-healthcare professionals. This study, carried out by European Union of Medicine in Assurance and Social Security (EUMASS), aimed to describe and compare the use of task transfer (task shifting, delegation and support) in European social security systems. The approach was threefold: (1) A survey questionnaire was sent to all 20 EUMASS members, inquiring about the present and planned use of task transfer in work disability assessments, and how it has been evaluated; (2) A literature study was undertaken on task transfer; (3) Case studies were carried out in selected countries (Belgium, France, the Netherlands, Norway, the United Kingdom) where different approaches to task transfer have been used. Task transfer in disability assessments has been introduced in seven countries, mostly in Western Europe. A mixture of task shifting, delegation, and support was often used. Nurses were the main group to take over new tasks, but other (non)-healthcare professionals were also involved. Task transfer is implemented in different ways in line with the cultural traditions and the specific organisations that comprise the political and financial framework of the individual country. Education and training were important for a successful change of tasks. The changes were mostly seen as positive. Innovative and flexible approaches are described which can provide examples for other countries and can inform further study.